Noradrenaline acting on astrocytic β-adrenoceptors enhances neuronal complexity in primary cortical neurons - Day, Jennifer (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
The complex structure of a neuron, comprising of an axon and dendrites (collectively termed neurites), is integral to the formation of functional networks in the central nervous system during development and after injury. Understanding the mechanisms involved in neuritic growth is imperative for regenerative neuroscience, and may lead to symptomatic cures for neurodegenerative diseases.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin